2019
DOI: 10.1017/s0890060419000143
|View full text |Cite
|
Sign up to set email alerts
|

Saving energy by anticipating hot water production: identification of key points for an efficient statistical model integration

Abstract: This work aims to evaluate the energy savings that can be achieved in domestic hot water (DHW) production using consumption forecasting through statistical modeling. It uses our forecast algorithm and aims at investigating how it can improve energy efficiency depending on the system configuration. Especially, the influence of the DHW production type used is evaluated as well as the water tank insulation. To that end, real consumption measurements are used for model training. Then simulations are run on using T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Artificial intelligence (AI) and machine learning (ML) algorithms thrive on data, and the quality and size of the dataset significantly impact the performance and applicability of these models in realworld scenarios. Researchers emphasize the importance of large, high-quality datasets to train algorithms that can make accurate predictions and decisions across different situations [100,138,139]. It is evident that data privacy is essential in the realm of electrical water boilers' energy consumption prediction, surpassing the relevance of data quality, availability, and privacy.…”
Section: Data and Measurement Techniques For The Prediction Of Electr...mentioning
confidence: 99%
“…Artificial intelligence (AI) and machine learning (ML) algorithms thrive on data, and the quality and size of the dataset significantly impact the performance and applicability of these models in realworld scenarios. Researchers emphasize the importance of large, high-quality datasets to train algorithms that can make accurate predictions and decisions across different situations [100,138,139]. It is evident that data privacy is essential in the realm of electrical water boilers' energy consumption prediction, surpassing the relevance of data quality, availability, and privacy.…”
Section: Data and Measurement Techniques For The Prediction Of Electr...mentioning
confidence: 99%
“…The authors recorded 97% of the DHW usage profiles and 92% of the electricity usage profiles as a correlation between the simulated and calculated results. Using consumption forecasting through statistical modelling, Denis et al [28] evaluated the energy savings that can be achieved in DHW output. The authors reported the energy savings of 3.6% to 12.8%.…”
Section: Motivation Of This Reviewmentioning
confidence: 99%
“…ML evolved from Artificial Intelligence (AI). ML methods are used to characterize algorithms that learn from existing data and these algorithms use a large amount of data for the learning process with a very limited number of input features [28]. There are three major ML methods available for behavioural analysis.…”
Section: Overviewmentioning
confidence: 99%